CCSK Cert Prep: 5 Application Security and Identity Management for Cloud Computing. - Lachance, Daniel (linkedin.com, 2021)
Advance your preparation for the CCSK exam and learn the skills you need to keep applications secure and provide identity management for cloud-based applications.